ANALYZING THE DEIXIS OF SOUNDTRACK SONG OF MULAN “REFLECTION” - Rizky Putri Jasmine; Sudiyono Sudiyono (PROJECT (Professional Journal of English Education), 2023)
The objectives of this study are to identify and analyze the different types of deixis that are utilized in the song lyric, as well as to determine which deixis is the most prevalent. The writers chose Christina Aguilera’s song entitled Reflection that rising to the top again nowadays which composed in beautiful lyric that touch listeners’ heart. The qualitative research method was applied in this study. There are three sorts of deixis, according to the findings: personal deixis, temporal deixis, and spatial deixis. Based on discussion, personal deixis is the dominant in the lyric with 72.31% chances appearing compare to the rest.